The impact of interleukin-6 (IL-6) and mesenchymal stem cell-derived IL-6 on neurological conditions - Kerkis, Irina; Silva, Álvaro Prieto da; Araldi, Rodrigo Pinheiro (Frontiers in Immunology, 2024)
Interleukin-6 (IL-6) is a versatile cytokine crucial for immune response modulation, inflammation regulation, and various physiological processes in the body. Its wide-ranging functions underscore its importance in maintaining health. Dysregulated IL-6 is closely associated with many diseases, making it a key research and therapeutic target. Elevated IL-6 levels in the central nervous system worsen neuroinflammation in neurodegenerative diseases by activating microglia and astrocytes and releasing pro-inflammatory cytokines and neurotoxic molecules. Moreover, dysregulated IL-6 weakens the blood-brain barrier, exacerbating neuroinflammation and neuronal damage by allowing peripheral immune cells and inflammatory mediators to enter the brain. Mesenchymal stem cells (MSCs) show promise in modulating neuroinflammation by regulating IL-6 levels. They effectively suppress pro-inflammatory cytokines, including IL-6, while promoting anti-inflammatory factors. This therapeutic approach highlights the importance of targeting IL-6 and other inflammatory mediators to alleviate neuroinflammation and its adverse effects on neurological disorders. This review provides a comprehensive overview of IL-6’s involvement in neurological disorders, examining endogenous IL-6 and IL-6 derived from MSCs. We explore IL-6’s mechanisms affecting neuronal function, survival, and immune modulation in the central nervous system. Additionally, we discuss the potential of MSC-derived IL-6 in neuroregeneration and neuroprotection. By elucidating IL-6’s interplay with neurological pathologies, this review offers insights into novel therapeutic strategies targeting IL-6 signaling pathways for neurological disorders.